The Art of Theoretical Biology - Matthäus, Franziska 1975-; Matthäus, Sebastian; Harris, Sarah; Hillen, Thomas 1966- (Springer, 2020)
This beautifully crafted book collects images, which were created during the process of research in all fields of theoretical biology. Data analysis, numerical treatment of a model, or simulation results yield stunning images, which represent pieces of art just by themselves. The approach of the book is to present for each piece of visualization a lucid synopsis of the scientific background as well as an outline of the artistic vision
From the content: The Deadly Beauty of Cancer.- Cellular Connections.- Annealing Party.- Cells on the Ferris Wheel.- The Magic Pants that Always Fit.- Racing Triangles.- Rising Dragons.- Henri in Wonderland.- Peak of the Iceberg.- Guiding Spiral.- The Hidden Beauty of Roots.- The Beauty of a Beast.- The Ghost.- Lymph Node Landscapes.- Breezing Drops.- Labyrinths: Exotic Patterns of Cortical Activity.- Mammalian Lipidomic Network.- One Step at a Time.- How a Tumor Gets its Spots.- Patchwork Patterns.- Cancer Warfare.- Collective Decision Making.- Cell Simulation in Blossom.- Semblance of Heterogeneity.- Can we Crack Cancer?.- Dance with Predators and Prey.- Knitting Proteins.- Nothing Stands Still in the Streams of Life.- Restless Mind Wandering.- Morphological Echoes.- Cancer as a Killer Tsunami.- Cells Are Watching You.- Roots or Flowers? Take a Guess.- Spectral Forms and Cosmic Storms.- Antigenic Explosion.- Crop Circles of Cancer.- Scalp.- Coupled Invasion.- Lost in the Cells.- Becoming Important.- Community Matters.- Acidic Dance.- Flocking, Swirling and Spinning Stars in a Cell.- A Mosaic of Cancer and Liver Tissue.- Cell Firework.- Pulled in Line.- Convergence.- Arctic Breeze.- Extracellular Galaxies.- Oriental Landscape Painting byPredator Species.- Life is Lived on the Edge.- Cellular Swarms in Cellular Automata.- Bumps, Ridges, and no Flows in Vein.- Growing Orbs /Mingled Metabolism.- Out of the Comfort Zone.- Green Protein Interaction Wheel.- Vincent van Gogh’s Autocatalysis.- Clonal Inferno.- What Lies Beneath (the Heartbeat).- Tree of Life.- Tower of Life.- Clone Wars - The Immune System Awakens.- Modelled Cell.- CD196-.- Tumor Composition Depends on the Viewing Angle.- Poincaré’s Homoclinic Horror.- E A S (Evolving Asteroid Starships).- Interacting Spider Webs.- Heart Cells areaMAZEing.- Actin Spring.- Dynamical Diggers.-
Keywords: bicssc; bisacsh; Systems biology; Mathematics; Visualization; Fine arts; Bioinformatics; Life sciences; Theoretische Biologie; Visualisierung; Schönheit; Bildwissenschaft; Hardcover, Softcover / Biologie; Bildband